O trabalho como formação e deformação do homem nos manuscritos de 1844 de karl Marx - Silva, Antônio Carlos da Costa e (2012)
The research that gives a particular shape to this dissertation had as its goal to investigate Marx’s double perspective of work in his Economic Philosophic Manuscripts of 1844, viz, labor as former and deformer of man. In order to carry on this qualitative, biographic and documentary research, the task was based on an immanent analysis of the aforementioned document by the use of the dialectic-critical-reflexive method. The study was aimed at evaluating the issue of private propriety as a condition to negated labor in so far as it investigates Marx’s critical appraisal not only of Political Economy but also of Hegel’s dialectics. In this way the research tries to show that Marx’s reflection in the 1844 manuscripts allows for that double perspective of labor as a negation/deformation of man within estranged labor (activity of subsistence and immediate satisfaction as a factor of man’s dehumanization). Therefore, labor does not represent an activity by means of which man educate and form himself materially and spiritually, but as an instrument that alienates him from his production, his activity, even from himself. On the other hand, one sees the positive concept of labor as an affirmative activity that validates life and the individual within a social framework. Marx propounds that man asserts himself in his job as far as it objectifies his essential strength that is a previously established output engendered by an anticipating awakening of his critical will and in this fashion releases its generic/universal appeal. One concludes then that for Marx, labor is essentially a creative activity (forming) for man, while in the capitalist society which is based on private propriety of the means of production, labor is changed into a tool for negation of man and denial of human formation.